2004
DOI: 10.1291/hypres.27.599
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aberrant Iron Homeostasis in the Upregulation of Transforming Growth Factor-β1 in the Kidney of Angiotensin II-Induced Hypertensive Rats

Abstract: We have previously shown that abnormal iron metabolism might be one underlying mechanism of the renal damage observed in the angiotensin II-infused rat. Transforming growth factor-1 (TGF-1) is known to play a crucial role in the development of renal damage induced by activation of the renin-angiotensin-aldosterone system. The purpose of the present study was to examine the effects of an iron chelator and a free creases the renal expression of TGF-β in animal models of glomerulosclerosis (2, 3), hypertension (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…1, 2); these results stood in contrast with the exclusive co-localization of ferritin and heme oxygenase-1 (15). In addition, only a fraction of the mRNA expression of the genes tested was colocalized with lipid deposition, again in contrast to the exclusive co-localization of TGF-β1 mRNA and lipid deposition in the kidney (16,17).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…1, 2); these results stood in contrast with the exclusive co-localization of ferritin and heme oxygenase-1 (15). In addition, only a fraction of the mRNA expression of the genes tested was colocalized with lipid deposition, again in contrast to the exclusive co-localization of TGF-β1 mRNA and lipid deposition in the kidney (16,17).…”
Section: Discussionmentioning
confidence: 91%
“…Although expression of the transferrin receptor (TfR) (9, 10), DMT1 (11,12), FPN (13), and hepc (14) has been demonstrated in the kidney, information about the physiological importance and the regulation of these genes has been limited to date. We previously reported that the administration of angiotensin II to rats causes prominent iron deposition in the kidney, which occurs primarily in the proximal tubular epithelial cells; this deposition is thought to be associated with increased proteinuria and the upregulation of fibrosis-related genes (15,16). Here, we have characterized the renal expression patterns of these iron metabolism-related genes and investigated how their expression might be regulated by angiotensin II in the kidney.…”
Section: Introductionmentioning
confidence: 98%
“…Unilateral ureteral obstruction (UUO) is a model of renal fibrosis that mimics many aspects of obstructive nephropathy, including cellular infiltration, tubular proliferation and apoptosis, myofibroblast accumulation and increased ECM deposition (17)(18)(19). Some genetically engineered mice that are considered to influence the degradation of ECM have been studied by UUO.…”
Section: Tissue Inhibitor Of Metalloproteinase-3 Plays Important Rolementioning
confidence: 99%
“…Such studies demonstrate that ANG II, so administered, provokes markedly increased systemic arterial pressure, reduces glomerular filtration rate (GFR), increases urinary protein excretion, induces the expression of proinflammatory and other damaging genes, and provokes proliferation as well as apoptosis of tubular epithelial cells (3,4,11,36). However, many of these studies, including the initial studies by us and others demonstrating renal induction of HO-1 by ANG II in vivo, have employed pressor dosages/regimens of ANG II that lead to markedly elevated plasma levels of ANG II.…”
mentioning
confidence: 99%